Potencial fisiológico de genótipos de arroz de terras altas em condições de déficit de nitrogênio - Belo, Weydson Araujo (2020)
In Maranhão, rice is grown in almost all municipalities, the highland ecosystem predominates, but its yield in relation to irrigated rice is much lower. Nitrogen is the macronutrient that limits upland rice production. Therefore, the objective of this work was to evaluate the physiological potential of upland rice genotypes under nitrogen deficit conditions. The experiment was carried out in a greenhouse, in plastic pots with 10 kg of soil in each. The substrate used came from the soil of the school farm of the State University of Maranhão. A randomized block design with an 8x2 factorial scheme with three replications was used, and the treatments consisted of two levels of N, that is, without application of N (low) and an application of 800 mg N kg-1 (high) of soil, using urea and eight upland rice genotypes. The evaluations were made at 51, 80 and 100 days after planting when the parameters of gas exchange, photochemical efficiency and the SPAD index were determined. At physiological maturation, grain yield was determined. In general, nitrogen deficiency did not significantly affect the assessed physiological variables and consequently the production. But the nitrogen-free genotypes G2, G4, G5 and G6 alone had results that help to achieve satisfactory productivity in environments with nitrogen deficit.